The Effect of The Teams Games Tournament Type Cooperative Learning Model on Students’ Learning Motivation in IPAS Learning For Fourth-Grade Students of Inpres 1 Birobuli Public Elementary School - Mifta Ahmad Buhari Lapabande; Nashrullah Nashrullah; Arif Firmansyah; Muchdar Muchdar (Journal of Educational Sciences, 2026)
This study investigates how the Teams Games Tournament cooperative learning model can improve the learning motivation of fourth grade students in Social Studies at Inpres 1 Birobuli Public Elementary School. The research aims to determine whether combining teamwork, friendly competition, and enjoyable activities can encourage students to participate more actively in the learning process. A quantitative approach with a Quasi Experimental design is applied, where class IVA receives the Teams Games Tournament treatment and class IVB functions as the comparison group. A motivation questionnaire is used to collect data after the learning activities. Before testing the hypothesis, the data are examined through normality and homogeneity tests to ensure statistical requirements are met. The hypothesis is then analyzed using the Paired Sample T Test through SPSS Statistic twenty five. The results show a significance value of zero point zero zero zero, lower than the alpha level of zero point zero five, leading to the acceptance of the alternative hypothesis. These results indicate that the Teams Games Tournament model significantly increases students motivation and creates a more engaging classroom atmosphere.